The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1177/014662168400800305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Difficulties and Reliabilities of Quantitative Word Problems in Completion and Multiple-Choice Item Formats

Abstract: Quantitative word problems were written as parallel completion and multiple-choice items, and were administered to 232 undergraduate students to compare the reliabilities and item difficulties associated with these formats. The multiple-choice options were written using specific numerical responses for each of five alternatives, revised by replacing the fifth option with "none of the above," and also by replacing each of the five responses with ranges of numerical values.Differences in distributions of scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…We found that NOTA significantly increased difficulty when it replaced the key. This finding is consistent with previous studies that have demonstrated an increase in difficulty with inclusion of NOTA (Crehan & Haladyna, 1991;Dudycha & Carpenter, 1973;Oosterhof & Coats, 1984;Tollefson, 1987). However, unlike all but a select few studies (Dudycha & Carpenter, 1973;Rich & Johanson, 1990), we have demonstrated a decrease in discrimination coefficients following NOTA inclusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that NOTA significantly increased difficulty when it replaced the key. This finding is consistent with previous studies that have demonstrated an increase in difficulty with inclusion of NOTA (Crehan & Haladyna, 1991;Dudycha & Carpenter, 1973;Oosterhof & Coats, 1984;Tollefson, 1987). However, unlike all but a select few studies (Dudycha & Carpenter, 1973;Rich & Johanson, 1990), we have demonstrated a decrease in discrimination coefficients following NOTA inclusion.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies have found that NOTA increases test difficulty (Crehan & Haladyna, 1991;Dudycha & Carpenter, 1973;Forsyth & Spratt, 1980;Knowles & Welch, 1992;Oosterhof and Coats, 1984;Rimland, 1960;Tollefson, 1987;Wesman & Bennett, 1946). However, it is important to distinguish between the presence of NOTA as the key or as a distractor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in item discrimination were reported by Forsyth and Sprat (1980), Oosterhof and Coats (1984), and Tollefson and Tripp (1983). But, Crehan and Haladyna (1991), Crehan, Haladyna, and Brewer (1993), Dudycha and Carpenter (1973), Frary (1991) and Tollefson (1987) did not find differences in item discrimination.…”
Section: Previous Research On Nota Itemsmentioning
confidence: 71%
“…These investigations were at some point contradictionary. Some reported differences in difficulty when using the NOTA option in comparison with a conventional option (Crehan & Haladyna, 1991;Crehan, Haladyna, & Brewer, 1993;Dudycha & Carpenter, 1973;Forsyth & Spratt, 1980;Frary, 1991;Oosterhof & Coats, 1984;Tollefson, 1987). Sometimes the differences were statistically significant, but not always.…”
Section: Previous Research On Nota Itemsmentioning
confidence: 99%